Dental and skeletal changes occurring after orthodontic-surgical treatment of mandibular prognathism - Čutović, Tatjana; Ilić, Jana; Adamović, Tijana; Matijević, Stevo; Radojičić, Julija; Stošić, Srboljub (Vojnosanitetski pregled, 2023)
Background/Aim. Mandibular prognathism (MPG) is a severe form of facial and jaw deformity. This kind of anomaly usually requires combined orthodontic-surgical treatment. The aim of this study was to determine the changes in the craniofacial complex after orthodontic-surgical treatment of patients with MPG by analyzing the cephalometric parameters on teleradiography images before and after treatment. Methods. The study included a sample of 40 subjects (mean age 24.1 ± 4.1 years) who underwent orthodontic-surgical treatment of MPG. Vertical and sagittal parameters which characterize MPG were measured on profile teleradiography images before and 12 months after treatment. Based on the analysis of cephalometric parameters on preoperative and postoperative teleradiography images, dental and skeletal changes that occurred after treatment were determined. Results. After the end of the treatment, most of the parameter values that characterize MPG were significantly reduced. A drop in values was noted in the following parameters: SNB, SNPg, NS/SpP, NS/MP, SpP/MP, NSAr, ArGoMe, Bjork polygon, NMe, NSna, SnaMe, SSnp, I/SpP. There was a statistically significant increase in the values of the following parameters SNA, ANB, GoArNS, SGo and i/MP. No significant changes in values were recorded on the OP/NS and SArGo parameters. Conclusion. Orthodontic-surgical treatment of MPG leads to changes in the bone and dental structures of the craniofacial system. As a result of such treatment, there is a functional improvement and an improvement in the appearance of the face.